Innovation in Language Teaching and Learning The Case of Japan - Reinders, Hayo; Ryan, Stephen; Nakamura, Sachiko (New Language Learning and Teaching Environments,, 2019)
This book examines a wide range of innovations in language learning and teaching in Japan. Each of the chapters describes the impetus for a change or new development in a particular context, from early childhood to adult learning, details its implementation and provides an evaluation of its success. In doing so, they provide a comprehensive overview of best practice in innovating language education from teaching practice in formal classroom settings, to self-directed learning beyond the classroom, and offer recommendations to enhance language education in Japan and beyond. The book will be of interest to scholars of applied linguistics and language development, and in particular to those involved in managing change in language education that attempts to mediate between global trends and local needs. Hayo Reinders is TESOL Professor and Director of the doctoral programme at Anaheim University, USA and Senior Research Advisor to Kanda University in Tokyo, Japan. Stephen Ryan is a professor in the School of Culture, Media and Society at Waseda University in Tokyo, Japan. Sachiko Nakamura is a doctoral candidate in Applied Linguistics at King Mongkut's University of Technology Thonburi, Thailand. .